The Lesson from the First Italian Lockdown: Impacts on Anxiety and Depressive Symptoms and Sleep Quality in Patients with Remission of Inflammatory Bowel Disease - Spina, Annamaria; Mazzarella, Chiara; Dallio, Marcello; Romeo, Mario; Pellegrino, Raffaele; Durante, Tommaso; Romano, Marco; Loguercio, Carmelina; Di Mauro, Maurizio; Federico, Alessandro; Gravina, Antonietta G. (Reviews on Recent Clinical Trials, 2022)
Background: During the COVID-19 pandemic in Italy, decisions were taken to adopt restrictive legislative measures, such as the first half of the 2020 lockdown. In those months, patients with inflammatory bowel disease experienced social isolation and reduced access to health care. Objective: We aimed to evaluate, in this condition, the presence of remission subgroups that were most impacted by the lockdown. Methods: During the first Italian lockdown, we recruited patients with remission of inflammatory bowel disease by administering an online questionnaire including patient demographics, the Beck Anxiety Questionnaire Inventory, the Beck Depression Inventory questionnaire, and the Pittsburg Sleep Quality Index, all validated standardized questionnaires for anxiety symptom levels, depression, and sleep quality. Results: Our results showed how female patients (p<0.0001) with Crohn’s disease (p<0.001) experienced worse levels of anxiety symptoms. Female patients (p<0.0001) between 50 and 60 years of age (p=0.013) with Crohn’s disease (p=0.047) experienced worse levels of depressive symptoms. Females also experienced significantly worse sleep levels (p<0.001). We found a correlation between the number of sleeping hours (p<0.001) and the time taken to fall asleep (p<0.001) and the Beck Anxiety Questionnaire Inventory,which showed a linear worsening of the number of minutes it took to fall asleep, and the Beck Depression Inventory questionnaire. Conclusion: Among patients with remission of inflammatory bowel disease, female patients, patients with Crohn’s disease, and people aged between 50 and 70 years should be considered for screening for anxiety and depression disorders and an assessment of sleep quality.
Keywords: anxiety